A classical model of education, growth and distribution - Amitava Krishna Dutt; Roberto Veneziani (Queen Mary University of London, School of Economics and Finance, 2017)
We develop a classical macroeconomic model to examine the growth and distributional consequences of education. Contrary to the received wisdom, we show that human capital accumulation is not necessarily growth-inducing and inequality-reducing. Expansive education policies may foster growth and reduce earning inequalities between workers, but only by transferring income from workers to capitalists. Further, the overall effect of an increase in education depends on the actual characteristics of the educational system and on the nature of labor market relations. We argue that the model can shed light on some recent stylized facts on growth, distribution and education for the US.
Keywords: O41; I24; E25; 330; Education; Growth; Distribution